A Critical and Comparative Analysis on the Effect of Business Rescue on Creditors’ Rights against Sureties - Tsangarakis, Andreas (Department of Commercial Law, 2019)
Business rescue proceedings have been introduced into South African company law under chapter 6 of the Companies Act 71 of 2008. The United States Chapter 11 bankruptcy model was closely consulted by the legislature when drafting chapter 6. Further to this and although business rescue has been generally well received, there have been legal issues which have arisen in the interpretation of chapter 6. In particular, the issue of creditors' rights against third party sureties of financially distressed companies continues to fall under the spotlight which, in tum, has caused a ripple of commercial uncertainty to filter through to creditors. This issue will be investigated with comparative reference to the position in the United States. In doing so, a critical analysis will be undertaken of the procedures and processes in both of these jurisdictions, whereafter a comparative analysis will be presented. It will be advocated that although the essential difference between the two jurisdictions is the United States' legislative regulation on this issue, South African courts have correctly decided on creditors' rights against third party sureties. Unlike in the United States where conflicting decisions have been delivered, commercial certainty on this issue does in fact exist in South Africa notwithstanding the lack of statutory regulation under the Companies Act. It will be further advocated that although there is potential for this issue to be development under the South African common law when having regard to the decisions in the United States, caution is to be exercised as such development may generate commercial uncertainty.